(untitled) (TERRA LATINOAMERICANA, 2026)
The municipalities located in the southern region of Córdoba exhibit high potential for the development of cacao cultivation (Theobroma cacao L.), whose productivity depends on specific edaphic conditions. In this context, it is essential to assess whether the soils in southern Córdoba meet the optimal conditions for the establishment and growth of the crop. This study aimed to characterise the physico-chemical properties of cacao-growing soils and to identify their main limitations. The research was conducted in 2022 across four municipalities—Tierralta, Valencia, Montelíbano, and Puerto Libertador—where 111 cacao farms of varying ages (5 to 25 years) were assessed using a quantitative approach, including field and laboratory evaluations of soil physico-chemical parameters. No signs of compaction were observed, which was consistent with low bulk density (Da) values; the predominant textural class was clay loam (F-Ar). The soil pH presented slightly acidic values that were restrictive for cacao cultivation in Montelíbano and Puerto Libertador.Phosphorus (P) content was low (<15 mg kg–¹), with high variability (CV > 100%). Organic matter showed medium to high levels, and cation exchange capacity (CEC) values were high across most of the evaluated sites. Some chemical limitations were identified, mainly in Montelíbano and Puerto Libertador. Overall, the results suggest that the study area presents suitable edaphic conditions for cacao cultivation.